The Nuclear Non-proliferation Treaty in Jeopardy? Internal Divisions and the Impact of World Politics. Issue 1 (2nd January 2017) - Müller, Harald
Abstract: The frustration of non-nuclear weapon states about the lack of progress in nuclear disarmament has reached boiling point: a vast majority of them have supported a resolution in the UN General Assembly that establishes a negotiation forum for concluding a prohibition of nuclear weapons in 2017. Rising tension among the nuclear powers and populist movements feeding nationalist emotions make it unlikely that the situation will change for the better in the near future. It is thus possible that the NPT might be eroded or, in the worst case scenario, simply collapse because of diminishing support.